Profile and working conditions of dental assistants in Marikina City - Banzon, Marie Cristine Denise
Introduction. A dental assistant is expected to be responsible for a variety of duties in the dental office. As ascertained by their title, a dental assistant will assist the dentist during procedures and performs laboratory work and clerical duties. This study aimed to describe the profile of dental assistants in Marikina City.